Methodology For The Artisanal Production Of Bokashi In A Cashew Nut Crop: A Case Study - Castaño, Juan Camilo Cardona; MEZA, Alejandra Margarita Olmedo; Zona, Martha Lamprea (International Journal of Environmental, Sustainability, and Social Science, 2026)
This research focuses on the need to develop a composting methodology for Anacardium occidentale (cashew) cultivation, aiming to optimize production and offer an alternative during times of input scarcity and high costs. This research stems from the need to find sustainable and economical solutions for farmers. The research was conducted in an exploratory and diagnostic manner. Farmers participated in the construction of the bokashi compost pile at the Namasté farm, using raw materials from the production unit. A statistical inference analysis was performed using linear regression and correlation tests. The dependent variables, temperature and pH, were analyzed. It was established that temperature affects the composting phases, allowing the proposed method to be tested and proven useful. The efficiency of bokashi composting for A. occidentale (cashew) cultivation was found. The dependent variables, temperature and pH, were analyzed. Agricultural production was optimized through the use of bokashi composting. The objective of proposing a composting methodology for A. occidentale (cashew) cultivation was achieved. The proposed method can be further studied, experimented with, and explored, as it has yielded excellent results. Bokashi composting is an economical and easy-to-implement alternative for optimizing agricultural production. This research contributes to the sustainability and economic well-being of farmers.